Anthrax as the cause of preseptal cellulitis - Celebi, S; Celebi, H; Celiker, UO; Kandemir, B; Alagoz, G; Esmerligil, S (Scriptor Publisher, 1997)
Anthrax is an infectious disease caused by Bacillus anthracis, It is primarily a disease of domestic animals such as cattle, goats, and sheep; but humans can rarely be infected by contact with infected animals or contaminated animal products, Our case is a 4-year-old boy who was initially diagnosed as preseptal cellulitis, but later he showed the characteristic anthrax lesions with a black necrotic eschar, Scrapings from the necrotic tissue showed gram positive rods and culture grew Bacillus anthracis, The patient responded to intravenous administration of penicillin G, and the lesions resolved, leaving a scar on the fight upper eyelid, Eyelid involvement of anthrax is rarely seen in clinical practice, but should be considered in differential diagnosis.
Keywords: cutaneous anthrax; eyelid; cicatricial ectropion; preseptal cellulitis